Front Cover: Cell Factory Design and Optimization for the Stereoselective Synthesis of Polyhydroxylated Compounds (ChemBioChem 4/2018). (30th January 2018) - Wiesinger, Thomas; Bayer, Thomas; Milker, Sofia; Mihovilovic, Marko D.; Rudroff, Florian
Abstract : The front cover picture shows an artificial metabolic mini‐pathway composed of an alcohol dehydrogenase and a dihydroxyacetone‐dependent aldolase for the synthesis of chiral aldol adducts in living Escherichia coli cells. Starting from primary alcohols, we designed and optimized this synthetic cascade on the genetic and on the down‐stream processing levels. The combination resulted in the synthesis of various chiral diols in up to 90% yield over two reaction steps. More information can be found in the full paper by F. Rudroff et al. onpage 361 in Issue 4, 2018 (DOI:10.1002/cbic.201700464 ).